A Comparison of the Effects of Reading Interventions on Engagement and Performance for Fourth-Grade Students With Learning Disabilities. (January 2015) - Bryant, Brian R.; Kim, Min Kyung; Ok, Min Wook; Kang, Eun Young; Bryant, Diane Pedrotty; Lang, Russell; Son, Seung Hyun
Inexpensive software applications designed to teach reading, writing, mathematics, and other academic areas have become increasingly popular. Although previous research has demonstrated the potential efficacy of such applications, there is a paucity of research that compares applications instruction (AI) with traditional teacher-directed instruction (TDI), and the relative effectiveness and efficiency of these instructional approaches remains largely unknown. This study used an alternating treatment design to compare academic engagement and outcomes (i.e., word identification and reading fluency) during an AI condition and a TDI condition for four students with learning disabilities (LD) attending a charter school. Instructional conditions (i.e., TDI, AI) were randomly alternated 7 times each, for a total of 14 instructional sessions. Results indicated that both approaches fostered high levels of engagement although students were more engaged during AI. With regard to academic performance, visual and quantitative analysis suggest that TDI was more effective than AI in terms of passage fluency and word identification. Students completed social validity rating scales to examine instructional preference. Results indicated that both approaches, TDI and AI, were popular with the students.